2019
DOI: 10.1016/j.jenvman.2019.02.079
|View full text |Cite
|
Sign up to set email alerts
|

Are dominant microbial sub-surface communities affected by water quality and soil characteristics?

Abstract: Subsurface microorganisms must deal with quite extreme environmental conditions. 13The lack of light, oxygen, and potentially nutrients are the main environmental stresses 14 faced by subsurface microbial communities. Likewise, environmental disruptions 15 providing an unbalanced positive input of nutrients force microorganisms to adapt to 16 varying conditions, visible in the changes in microbial community diversity. In order to 17 test microbial community adaptation to environmental changes, we performed a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 86 publications
(23 reference statements)
1
7
0
Order By: Relevance
“…In comparison, there were no significant differences among our samples, however, GW1 showed lower richness and overall phylogenetic distance than the other samples, but similar evenness with GW2. The alpha diversity of these groundwater wells is greater than has been reported for other groundwater aquifers, with Shannon Index values below 4 and as low as 0.47 having been reported for some [29,30]. The landfill leachate well and composite leachate cistern sample diversities are consistent with the findings of Stamps et al (2016), who showed high richness and evenness across the 19 U.S. landfills in their study.…”
Section: Discussionsupporting
confidence: 88%
“…In comparison, there were no significant differences among our samples, however, GW1 showed lower richness and overall phylogenetic distance than the other samples, but similar evenness with GW2. The alpha diversity of these groundwater wells is greater than has been reported for other groundwater aquifers, with Shannon Index values below 4 and as low as 0.47 having been reported for some [29,30]. The landfill leachate well and composite leachate cistern sample diversities are consistent with the findings of Stamps et al (2016), who showed high richness and evenness across the 19 U.S. landfills in their study.…”
Section: Discussionsupporting
confidence: 88%
“…In all cases, the biological processes are very active and many redox reactions are occurring simultaneously (Greskowiak et al, 2006). This phenomenon is enhanced in recharge applications, e.g., by the presence of a reactive layer of organic matter (Beganskas et al, 2018;Grau-Martínez et al, 2017;Valhondo et al, 2014), that could lead to biomass growth and bioclogging (Barba et al, 2019;Massmann et al, 2006;Perujo et al, 2018). Besides this, recharge processes are a relevant source of EOCs (here including UVFs) into aquifer systems (Kim et al, 2017;Laws et al, 2011;Maeng et al, 2011;Park and Lee, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Multivariate statistics is a suitable technique to treat big datasets involving different sorts of variables, from quantitative to categorical, and thus amenable to be used to combine biochemical, hydraulic, geological and external conditions (such as design, drilling characteristics. and maintenance) of water points (Barba et al, 2019b). Principal Component Analysis (PCA) is a multivariate statistics method which involves the analysis of a number of parameters or variables, revealing associations between them, known as (vario)factors or components.…”
Section: Multivariate Statistics Analysismentioning
confidence: 99%
“…For this reason, some variables from the initial dataset were grouped, transformed and/or eliminated. Following Barba et al, (2019b), non-Gaussian hydrochemical variables were transformed to log concentrations, these being Alkalinity, Eh (a proxy for redox conditions), and the concentrations of SO4 2-, Na + , Cl -, and SiO2. On the other hand, TOC (Total Organic Carbon), DO (Dissolved Oxygen), and the concentrations of NO3and NH4 + , were added to the analysis as raw data without any transformation (mostly based on a trial and error basis).…”
Section: Selecting Variables For the Statistical Analysesmentioning
confidence: 99%